Shining stars of vegetable cultivation in Sangrur (Punjab) under Farmer FIRST Programme - Singh, Kuldeep; Romana, Buta Singh; Kumar, Pankaj; Singh, Dalbeer (Indian Farming, 2022)
Vegetable cultivation as a potential enterprise could contribute towards enhancing the farmers’ income anduplifting their livelihood. Thus, under the Farmer FIRST Programme (FFP), farmers in the adopted village ofSangrur (Punjab) were introduced with improved high yielding varieties and advanced cultivation techniques.To popularize the high yielding varieties/hybrids of vegetables, advance techniques and low tunnel cultivation of vegetables were conducted in the adopted villages. Project team regularly provided guidance to the farmers which resulted into the remarkable success regarding vegetable cultivation. Some of the farmers became so successful that they became an inspiration for other farmers. These shining stars, Vinder Singh, Hakam Singh and Mandip Singh, cultivated the high yielding improved varieties and advanced cultivation techniques of vegetable cultivation. At first, they became successful and generated multi-folded income than rice-wheat crop rotation themselves and then, uplifted other farmers’ livelihood through farmer-to-farmer extension. They became inspiration for other farmers of their area and imparted vegetable cultivation skills to their fellow farmers and relatives, playing active role in crop diversification. Hence, it can be said that the vegetable cultivation module of the FFP is witnessing huge success in uplifting farmers’ livelihood through vegetable cultivation enterprise.